METIL EUGENOL, KHEMOTIPE DARIMINYAK ATSIRI Melaleuca spp. (MYRTACEAE) YANG TUMBUH DIKEBUN RAYA CIBODAS - Tri Murningsih; Chairul Chairul; Emma Sri Kuncari (Research Center for Biology-Indonesian Institute of Sciences, 2009)
The essential oils of the fresh leaves of Melaleuca spp. (M. alternifolia Cheel, M. ericifolia Sm., M. squarrosa Donn, and M.genistifolia Sm.) from Cibodas Botanical Garden, Indonesia were isolated by a hydrodistillation method and analysed by a gas chromatography/mass spectrometry (GC/MS) technique. The various Melaleuca species showed differences within their relative essential oil compositions. The oils from all samples were of the methyl eugenol (10.30-71.25%) chemotype. The others major constituent were terpinen-4-ol (38.49%), linalool (19.65%) and bis(2-ethylhexyl)phtalate (66.09%) in the M. alternifolia, M. ericifolia, and M. genistifolia respectively.